2017
DOI: 10.1080/08923973.2017.1320671
|View full text |Cite
|
Sign up to set email alerts
|

The anticancer effect of mebendazole may be due to M1 monocyte/macrophage activation via ERK1/2 and TLR8-dependent inflammasome activation

Abstract: Mebendazole (MBZ), a drug commonly used for helminitic infections, has recently gained substantial attention as a repositioning candidate for cancer treatment. However, the mechanism of action behind its anticancer activity remains unclear. To address this problem, we took advantage of the curated MBZ-induced gene expression signatures in the LINCS Connectivity Map (CMap) database. The analysis revealed strong negative correlation with MEK/ERK1/2 inhibitors. Moreover, several of the most upregulated genes in r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
30
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 23 publications
(35 citation statements)
references
References 42 publications
4
30
0
Order By: Relevance
“…Again, MBZ at 1-10 μM had little or no effect on cytokine release from non-activated PBMCs (Figure 3a ) but stimulated the release of several pro-inflammatory cytokines including TNFα, IL1β, IFNγ, IL6 from PBMCs activated by IL2 and anti-CD3 stimulation (Figure 3b ). This has clear resemblance with our previous study in which MBZ at low concentrations require priming with LPS to stimulate pro-inflammatory cytokine (primarily IL1β) release in the THP-1 model [ 18 ]. IL1β secretion is suggested to require two signals.…”
Section: Resultssupporting
confidence: 81%
See 1 more Smart Citation
“…Again, MBZ at 1-10 μM had little or no effect on cytokine release from non-activated PBMCs (Figure 3a ) but stimulated the release of several pro-inflammatory cytokines including TNFα, IL1β, IFNγ, IL6 from PBMCs activated by IL2 and anti-CD3 stimulation (Figure 3b ). This has clear resemblance with our previous study in which MBZ at low concentrations require priming with LPS to stimulate pro-inflammatory cytokine (primarily IL1β) release in the THP-1 model [ 18 ]. IL1β secretion is suggested to require two signals.…”
Section: Resultssupporting
confidence: 81%
“…Recently, we demonstrated that MBZ induce a pro-inflammatory tumour-suppressive M1 phenotype in THP-1 monocytes and macrophages. MBZ-induced IL1β release was found to be dependent on NLRP3 inflammasome activation and to involve toll-like receptor 8 (TLR8) stimulation [ 18 ].…”
Section: Introductionmentioning
confidence: 99%
“…Interestingly, others have demonstrated the induction of a more pro-inflammatory phenotype of macrophage using mebendazole. 24 , 25 In those experiments, mebendazole increased secretion of IL1b and TNF through activation of the ERK pathway. In our hands, ERK inhibition did not abrogate the macrophage-inducing effects of albendazole [data not shown].…”
Section: Discussionmentioning
confidence: 85%
“…Its anti-cancer properties were notably demonstrated in gliomas [11,14,27] and there is currently 3 ongoing clinical trials in high-grade gliomas in both adult and pediatric patients (NCT01729260, NCT02644291 and NCT01837862). Furthermore, a recent phase I trial demonstrated that administration of MBZ concomitantly with radiotherapy and temozolomide chemotherapy was safe in high-grade glioma patients [28] Although multiple studies have highlighted different mechanisms of action of MBZ in cancer cells [12][13][14][15][16], including its effects on the microtubule network [8,11,14,17,18], its precise molecular target(s) in tumor cells remained to be ascertained. Herein, we used in silico target prediction to unveil novel therapeutic targets for MBZ in GBM.…”
Section: Discussionmentioning
confidence: 99%
“…Several mechanisms of action have been proposed to explain the anticancer properties of MBZ. These include tumor angiogenesis inhibition [12,13], targeting of critical pathways involved in cancer such as Hedgehog signaling [14] and stimulation of anticancer immune response [15,16]. Most of these effects have been linked to the ability of MBZ to induce microtubule depolymerization in cancer cells [8,11,17,18].…”
Section: Introductionmentioning
confidence: 99%